Ensuring safety and sustainability of radiotherapy services during the COVID-19 pandemic in resources constrain country: An Indonesian experience. (September 2020) - Handoko,; Permata, Tiara Bunga Mayang; Giselvania, Angela; Nuryadi, Endang; Octavianus, Steven; Jayalie, Vito Filbert; Nicholas,; Khumaesa, Novi Elis; Maharani, Putri; Djuita, Fielda; Wijaya, I.G.A.G. Mahendra; Wahyono, Yuddi; et al.
Highlights: Status of radiotherapy centers in Indonesia. Radiotherapy adjustment during COVID-19 outbreak in Indonesia. Strategies for RT centers in Indonesia to cope with backlog during and after COVID-19 pandemic. Abstract: The global COVID-19 pandemic has placed a significant burden on the healthcare sector, overwhelming health services in affected countries worldwide. As healthcare facilities reorganize their services to adapt to this challenging problem, it is important that the sustainability of essential oncology services, including radiotherapy, is maintained. This article describes the Indonesian experience in ensuring sustainability of radiotherapy services during the pandemic, highlighting various important adjustments which were made to allow radiotherapy centers nationwide to continue operating while protecting staff and patients from the risk of disease transmission. As the backlog of patients waiting to start treatment will inevitably grow, some insight on how to proactively manage this issue will also be described.